2021
DOI: 10.1007/s11030-021-10188-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular docking, binding mode analysis, molecular dynamics, and prediction of ADMET/toxicity properties of selective potential antiviral agents against SARS-CoV-2 main protease: an effort toward drug repurposing to combat COVID-19

Abstract: The importance of the main protease (M pro) enzyme of SARS-CoV-2 in the digestion of viral polyproteins introduces M pro as an attractive drug target for antiviral drug design. This study aims to carry out the molecular docking, molecular dynamics studies, and prediction of ADMET properties of selected potential antiviral molecules. The study provides an insight into biomolecular interactions to understand the inhibitory mechanism and the spatial orientation of the tested ligands and further, identification of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 71 publications
0
21
0
Order By: Relevance
“…Several in silico docking studies suggested a direct interaction of GR and GA to these key players in virus internalization and replication: ACE2 [61][62][63], spike protein and its RBD [63][64][65][66], and 3CLPro [63,65,[67][68][69][70][71][72][73][74]. Only a few in silico analyses were negative (3CLpro [68,75], Spike [76]).…”
Section: Effects On Covid-19 Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several in silico docking studies suggested a direct interaction of GR and GA to these key players in virus internalization and replication: ACE2 [61][62][63], spike protein and its RBD [63][64][65][66], and 3CLPro [63,65,[67][68][69][70][71][72][73][74]. Only a few in silico analyses were negative (3CLpro [68,75], Spike [76]).…”
Section: Effects On Covid-19 Infectionmentioning
confidence: 99%
“…The main protease 3CLpro contains several canonical binding pockets, denoted P1-P4, in its active site [77]. In silico studies suggest the binding of GR to these pockets [63,[67][68][69][70][71][72][73][74]. However, when tested on enzyme activity, the results were contradictory.…”
Section: Effects On Covid-19 Infectionmentioning
confidence: 99%
“…Constant pressure, temperature and number of atoms were kept all through simulation. While pressure was kept 1.0 bar, temperature was maintained at 300 K using the proper algorithms [32,33]. However, before initiating molecular dynamics the systems were minimized as per standard guidelines.…”
Section: Futuristic Classical Molecular Dynamics Simulationmentioning
confidence: 99%
“…While a exible ligand can alter its conformation on binding the target site in a best possible manner, the protein can change its dynamics and conformation for promoting ligand binding [35]. Thus it is obvious that static approaches like molecular docking should be coupled to dynamic approaches like molecular dynamics simulations for gaining more insights about ligand-receptor stability [28,32]. We subjected celecoxib-COX-2 complex and ni umic acid-COX-2 for 10 ns simulation using the Desmond software.…”
Section: Celecoxib Showed More Interactions Over Ni Umic Acidmentioning
confidence: 99%
“… 20 Other compounds have been repurposed and tested on M Pro as well. 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 …”
Section: Introductionmentioning
confidence: 99%